Analisis Sistem Pengendalian Internal Atas Persediaan Barang Dagang (Sparepart) Dalam Upaya Mempertahankan Laba Pada PT. Selamat Lestari Mandiri - Putri Kharisma Andini; Andri Indrawan; Evi Martaseli (Fakultas Ekonomi Program Studi Akuntansi Universitas 45 Surabaya, 2024)
Putri Kharisma Andini (2030611037) Universitas Muhammadiyah Sukabumi. Analysis of the Internal Control System on Merchandise Inventory (Spareparts) in Efforts to Maintain Profitability at PT. Selamat Lestari Mandiri, supervised by Mr. Andri Indrawan, S.E., M.Ak. and Mrs. Evi Martaseli, S.E., M.Ak. This study aims to analyze the internal control system on merchandise inventory (spareparts) at PT. Selamat Lestari Mandiri in maintaining and increasing the company's profitability. The research employs a qualitative method with a descriptive approach to evaluate the procedures and effectiveness of the implemented internal control system. The results indicate that although the existing internal control system is has been effective in several aspects, improvements are still needed, particularly in inventory planning and supply chain management to ensure consistent stock availability. The analyzed internal control flowcharts and procedures cover the processes of receiving, storing, issuing, as well as monitoring and reporting spare parts inventory. By enhancing the effectiveness of the internal control system, the company can avoid losses due to stock shortages, thus maintaining and optimally increasing profitability.